2022
DOI: 10.1101/2022.05.06.490990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The proteomic and transcriptomic landscapes altered by Rgg2/3 activity in Streptococcus pyogenes

Abstract: Streptococcus pyogenes, otherwise known as Group A Streptococcus (GAS), is an important and highly adaptable human pathogen with the ability to cause both superficial and severe diseases. Understanding how S. pyogenes senses and responds to its environment will likely aid in determining how it causes a breadth of diseases. One regulatory network involved in GAS’s ability to sense and respond to the changing environment is the Rgg2/3 quorum sensing (QS) system, which responds to metal and carbohydrate availabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Our current study identified a QS-regulated transporter, Spy49_0460, whose expression leads to decreased transcription of at least three secreted virulence proteins: the pore-forming cytolysin, streptolysin O; the chemokine-cleaving protease, SpyCEP; and the antiphagocytic surface antigen, M protein. In support of these observations, a recent proteomics study from our lab confirmed that streptolysin O and M49 are significantly less abundant in the secreted fraction of proteins from QS-induced cells 18 . Spy49_0460 was previously identified in whole genome screens for genes important for virulence in a zebrafish model of necrotizing fasciitis 19, 20 , survival in human blood 21 and pharyngitis in a nonhuman primate model 9 , but the mechanisms underlying its importance in these models have not been determined.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our current study identified a QS-regulated transporter, Spy49_0460, whose expression leads to decreased transcription of at least three secreted virulence proteins: the pore-forming cytolysin, streptolysin O; the chemokine-cleaving protease, SpyCEP; and the antiphagocytic surface antigen, M protein. In support of these observations, a recent proteomics study from our lab confirmed that streptolysin O and M49 are significantly less abundant in the secreted fraction of proteins from QS-induced cells 18 . Spy49_0460 was previously identified in whole genome screens for genes important for virulence in a zebrafish model of necrotizing fasciitis 19, 20 , survival in human blood 21 and pharyngitis in a nonhuman primate model 9 , but the mechanisms underlying its importance in these models have not been determined.…”
Section: Discussionsupporting
confidence: 66%
“…This suggests that the downregulation of slo, spyCEP, and emm49 transcription could be due to an accumulation of changes in cell physiology or stress that lead to the observed phenotype. In support of this idea, our recent proteomics study also detected nucleotide stress and a link to the stringent response in QS-ON cells 18 . Alternatively, the Rgg2/3 regulon is induced within one hour of infection of the murine nasopharynx 10 , though little is known about its expression later in infection.…”
Section: Discussionmentioning
confidence: 59%